Vonoprazan and Helicobacter pylori Treatment: A Lesson From Japan or a Limited Geographic Phenomenon? - Amin Talebi Bezmin Abadi; Enzo Ierardi (Frontiers Media S.A., 2019)
Within a short time after the discovery of Helicobacter pylori, its critical role in many gastroduodenal disorders became evident. Many in vitro and in vivo data have proven that infection should be treated in order to avoid lasting colonization which may lead to problematic gastroduodenal diseases. Probiotics, preventive and therapeutic vaccines and antibiotic therapy are the main options proposed to cure these disorders. 25 years ago, triple therapy including a traditional proton pump inhibitor (PPI) and two antibiotics (amoxicillin and clarithromycin or metronidazole) was defined as the best therapy formulation for the H. pylori infection. With the strongly decreased effectiveness of this scheme, many empirical therapeutic regimens have been developed. However, the prevalence of resistance is increasing worldwide and reveals important geographic differences and even the most recent and effective regimens show some critical points. Therefore, efficacy of vonoprazan-based therapy in regions with low rate of clarithromycin resistance may be limited. In this review, we attempt to open a new window to overcome the problem of antibiotic resistance to H. pylori. In fact, we focused our attention on the possibility that conventional PPI may be replaced by vonoprazan, thus giving rise to the beginning of a new era characterized by an improved therapeutic option for H. pylori infection. Therefore, we hypothesize that switching to vonoprazan as a novel acid blocker for H. pylori treatment might allow an unexpected reassessment of the triple therapy, at least in regions with low rate of clarithromycin resistance. Nevertheless, this optimistic view of the problem could be disproved by the possible failure of vonoprazan based therapeutic regimens outside of Japan in geographic areas characterized by different rates of antibiotic resistances.